Герменевтические особенности основных типов коммуникации в традиционном танце - Николаенко, Д.А. (Культура народов Причерноморья, 2014)
Статья посвящена обоснованию типологии традиционных танцев по направлению
коммуникации. Такой выбор критерия продиктован методологической целесообразностью, а также
значительным влиянием коммуникативной составляющей на смысловое наполнение танца.
Предлагается выделять три основных типа: танцы с вертикальной, горизонтальной и многослойной
коммуникацией. В каждом из типов специфика адресата коммуникации определяет как технические
особенности танца, так и его символическое содержание. Представленная классификация
способствует расширению возможностей герменевтического подхода в исследовании танцевальных
культур. Стаття присвячена обґрунтуванню типології традиційних танців за напрямком комунікації.
Такий вибір критерію продиктований методологічною доцільністю, а також значним впливом
комунікативної складової на смислове наповнення танцю. Пропонується виділяти три основних типи:
танці з вертикальною, горизонтальною і багатошаровою комунікацією. У кожному з типів специфіка
адресата комунікації визначає як технічні особливості танцю, так і його символічний зміст. Подана
класифікація сприяє розширенню можливостей герменевтичного підходу в дослідженні танцювальних
культур. This article is devoted to the justification of the typology of traditional dances by the direction of
communication. This choice of the criterion dictated by the methodological expediency, as well as by the
significance of the influence of the communication component on the semantic content of the dance. It proposed
to allocate three basic types: dancing with the vertical, horizontal and multi-layer communication. Vertical
communication is conventionally monological: dancer does not exchange signals with another dancer, but
performs a dance for the observer. This is a ritual dance in which dancer appeals to a higher power, or scene
dance in which dancer pays a message to the viewer. Horizontal communication addressed from dancer to
dancer, not to the audience and not to the deity. This type of communication is typical for paired and group
everyday and festive dances. Multi-layer communication determined by the presence of two destinations. One
becomes a "fictitious", the other - this, which really turned the message. This is the type of communication
characteristic for ritual and scene dances. Any of the traditional dances, whatever the era and location it may
apply, necessarily belongs to one of the three types of communication. In each of the types of communication the
specificity of the recipient as the technical features of the dance and its symbolic content are determined.
Presented classification promotes opportunities of the hermeneutic approach in the study of dance culture.